Sistem Informasi Edukatif Anti-Bullying: Penerapan E-Modul di Panti Asuhan Mizan Amanah Surakarta - Budi Al Amin; Maria Atik Sunarti Ekowati; Rina Oktiyani; Ahmad Fauzi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Bullying is a form of social violence that can hinder children’s psychological and social development, especially in orphanage settings where residents come from diverse backgrounds. This study aims to develop and implement an educational information system based on an interactive e-module as a learning medium to prevent bullying at Mizan Amanah Orphanage Surakarta. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis phase involved observation and interviews to identify the forms and causes of bullying within the orphanage. The e-module was designed with an educational approach focusing on empathy, positive communication, and conflict resolution. The implementation results show that the anti-bullying e-module effectively improves students' understanding of bullying and fosters positive behavioral changes. This educational information system is considered effective as a digital learning medium that promotes a safe, harmonious, and bullying-free environment within the orphanage.